Arbidol hydrochloride compatibility study with starchy excipients using DSC, FTIR, TGA-FTIR, and PXRD methods - Rojek, Barbara; Bartyzel, Agata; Leyk, Edyta; Plenis, Alina (Journal of thermal analysis and calorimetry, 2025)
The broad spectrum of antiviral activity and relatively low toxicity of arbidol hydrochloride have made it an interesting subject of research. Additionally, there is no information available regarding its formulation with various excipients. Another drawback is its hydrophobic nature, which contributes to lower bioavailability in specific drug forms. Therefore, it is necessary to test its mixtures with excipients to identify those that can enhance its solubility in water. For this reason, tests of compatibility/incompatibility of mixtures of arbidol hydrochloride with starchy excipients such as dextrin, polydextrose, and hydroxypropyl starch were carried out using differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), thermogravimetry coupled with Fourier transform infrared spectroscopy (TGA-FTIR), and powder X-ray diffraction (PXRD). Additionally, phase diagrams were developed for arbidol hydrochloride mixtures with starchy polymers, which enabled prediction of the solubility of this active pharmaceutical ingredient (API) in polymers and the mutual miscibility of the ingredients. The study concluded that arbidol hydrochloride may be compatible with dextrin.